2015
DOI: 10.1179/1743294414y.0000000392
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and corrosion resistance of pulse electrodeposited Ni–Cr coatings

Abstract: In this study, Ni-Cr alloy coatings were obtained on mild carbon steel surface by direct current (DC) and pulse current (PC) electrodeposition from a kind of acid solution. X-ray diffraction (XRD), scanning electron microscope (SEM) and atomic force microscope (AFM) were used to analyse the phase structure and surface morphology. The microhardness of the Ni-Cr alloy coatings was evaluated using microhardness tester. The electrochemical behaviour of the Ni-Cr alloy coatings was investigated by polarisation curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…This dynamic mechanism results in an effect similar to the on-off periods in pulse plating; no deposition when there are excess ions (off time) and deposition when there is lack of (on time). In the actual pulse plating, pulse intervals increase the electrochemical polarisation of the cathode but deplete the electrolyte polarisation, meaning that nucleation energy of metal ions in solution over the substrate surface decreases, increasing nucleation rate, which results in many fine grains forming simultaneously [17]. Since there was no continuously applied current in the sc-method, deposited grains were not allowed to grow too large, achieving grain refinement.…”
Section: Resultsmentioning
confidence: 99%
“…This dynamic mechanism results in an effect similar to the on-off periods in pulse plating; no deposition when there are excess ions (off time) and deposition when there is lack of (on time). In the actual pulse plating, pulse intervals increase the electrochemical polarisation of the cathode but deplete the electrolyte polarisation, meaning that nucleation energy of metal ions in solution over the substrate surface decreases, increasing nucleation rate, which results in many fine grains forming simultaneously [17]. Since there was no continuously applied current in the sc-method, deposited grains were not allowed to grow too large, achieving grain refinement.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the potential deterioration of deposit quality in the process of grain refinement, pulsing is an effective method, and previous studies [1,14,17] have shown that pulse electrodeposition can be used to obtain a more uniform and dense coating while refining the grain size. Shen et al [18] maximised the control of the concentration polarisation by flushing the cathode surface with a strong electrolyte, leading to a better combination of tensile strength and ductility for NC Cu in an ultra-low sulphate concentration bath.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most important surface engineering coatings, Ni-based composite coatings possess superior resistance to oxidation, wear, and corrosion, and they are extensively used to cope with severe environments [1,2]. Particle reinforcements including nonmetallic and metallic particles (such as Al 2 O 3 , CeO 2 , Al, Cr, and Ti particles) can be co-deposited onto Ni deposits to establish Ni-based composite coatings by electrodeposition [1,[3][4][5][6][7][8][9]. The co-deposition behaviors of the particle additives contribute to an optimized microstructure, e.g., decreased crystallite size and diminished preferential growth orientation of nickel deposits, which consequently enhance the properties of the Ni composite coatings [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…The co-deposition behaviors of the particle additives contribute to an optimized microstructure, e.g., decreased crystallite size and diminished preferential growth orientation of nickel deposits, which consequently enhance the properties of the Ni composite coatings [5,9]. Among the particle additives, Cr particles are extensively adopted to fabricate Ni-Cr composite coatings with enhanced micro-hardness, high temperature oxidation, and corrosion and wear resistance [6][7][8]. Peng et al [1] electrodeposited Ni-Cr coatings and suggested that the Ni-Cr coatings possessed decreased crystallite size with respect to Ni deposits, which was induced by the co-deposition of Cr particles.…”
Section: Introductionmentioning
confidence: 99%